2019
DOI: 10.1590/1679-78255438
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Evaluation of Horizontally Curved Bridges Subjected to Near-Field Ground Motions

Abstract: Horizontally curved bridges have more complex seismic behavior than straight bridges and have been more vulnerable to earthquakes. The present study aimed to evaluate the seismic response of concrete bridges with straight and arched box girder decks in isolated and non-isolated states. The results indicated that increasing the curvature of the non-isolated bridge could increase the irregularity. In addition, increasing the curvature of the deck leads to an increase in shear force, bending moment, and displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Other parametric studies regarding the seismic response of curved steel I-girder bridges unanimously confrm that the radius of curvature had the most signifcant impact on the seismic performance of this class of bridges [22][23][24]. Minavand and Ashtiany [25] conducted a parametric study based on the model of Sadr Elevated Bridge, located in the northeast of Tehran, with a horizontally curved RC box-girder typology. Tey concluded that increasing the curvature of the deck leads to an increase in seismic displacement demand of piers, shear force, and bending moment demands of the deck and piers.…”
Section: Introductionmentioning
confidence: 99%
“…Other parametric studies regarding the seismic response of curved steel I-girder bridges unanimously confrm that the radius of curvature had the most signifcant impact on the seismic performance of this class of bridges [22][23][24]. Minavand and Ashtiany [25] conducted a parametric study based on the model of Sadr Elevated Bridge, located in the northeast of Tehran, with a horizontally curved RC box-girder typology. Tey concluded that increasing the curvature of the deck leads to an increase in seismic displacement demand of piers, shear force, and bending moment demands of the deck and piers.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained for the stability coefficient with all kinds of overturning axes in multi-span continuous curved box girders show that the anti-overturning performance is very strong because more support means more effective constraints on the structure, especially when the radius is small (Luo, X.,2018). Minavand, M., & Ghafory-Ashtiany, M. (2019) have modelled the box deck of Sadr Bridge located in Teheran in straight and horizontally curved forms with four central arc angles. They have modelled the bridge in non-isolated and isolated states with a friction pendulum bearing (FPB).…”
Section: Introductionmentioning
confidence: 99%